PENGEMBANGAN SISTEM INFORMASI PENDAFTARAN BEASISWA PENINGKATAN PRESTASI AKADEMIK (PPA) JURUSAN ILMU KOMPUTER FAKULTAS MATEMATIKA DAN ILMU PENGETAHUAN ALAM UNIVERSITAS LAMPUNG DENGAN MENERAPKAN ALGORITMA SORTING QUICK SORT DAN SELECTION SORT - Dwi Sakethi; Febi Eka Febriansyah; Novita Sari (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2015)
Information System of PPA Scholarship Registration at Department of Computer Science Faculty of Mathematic and Natural Science Universitas Lampung by applying Sorting Algorithm Quick Sort and Selection Sort is a system that is used to ease the processing of shcolarship data. A student who participates the selection of PPA scholarship registration at Department of Computer Science has to enter the registration data on this system, so that the Secretary of Department doesnâ€™t need to enter the applicantâ€™s scholarship registration data anymore. This system can also rank automatically by using two sorting methods Quick Sort and Selection Sort. This system is built by using PHP as the programming languange and MySQL. Based on running time sort and complexity of its algorithm, itâ€™s proved that Quick Sort Method is faster that Selection Sort Method. The result of functional testing data shows that the system can function in accordance with the requirement analysis. Based on non-fuctional testing data, it shows that at admin level of this system is include in category of â€œGoodâ€ with the average value of 4.20 and user (student) level of this system is include in category of â€œGoodâ€ with the average value of 3.97.